Currículo e inclusão de estudantes com transtorno do espectro do autismo : produção coletiva de artefato cultural e suas mediações pedagógicas - Feltrin, Maria das Graças Pereira (2022)
Through studies in the field of inclusive education and a critical analysis of the contemporary reality on the acknowledgment of the rights of people with Autism Spectrum Disorder (ASD), it appears, among other aspects, that the education of this public is still an arena under construction, scarred by different ways of covering development and educational possibilities, peculiar to each individual with this disorder. This study problematizes the role of the school curriculum in the inclusion of students with ASD and aims to: experience the Individualized Education Plan (IEP) as a curricular cultural artifact for the education of students with the disorder, in a process of collective elaboration and from the perspective of inclusive education. As a methodology, we used Collaborative Action Research, which has an empirical basis that enables a significant movement in educational reform and in establishing changes in the curriculum. Therefore, the aforementioned study consisted of conducting and monitoring the collective development of an IEP for the education of two students with ASD in a public school in Várzea Grande-MT, contextualized with the curriculum of the regular class, with pedagogical practices and with the Political-Pedagogical Project. Based on collective experience, this study shows that the subjects of a regular inclusive curriculum are not only students and teachers from the school, but the entire school community, which also includes families. This scientific investigation resulted in the re-signification of teaching practice based on the understanding of how the process of education and inclusion of students with ASD occurs and, thereby, provided them with greater participation and significant learning in the classroom along with their peers.